2010
DOI: 10.1021/la1035932
|View full text |Cite
|
Sign up to set email alerts
|

Origin of Lyotropic Liquid Crystalline Mesophase Formation and Liquid Crystalline to Mesostructured Solid Transformation in the Metal Nitrate Salt−Surfactant Systems

Abstract: The zinc nitrate salt acts as a solvent in the ZnX-C 12 EO 10 (ZnX is [Zn(H 2 O) 6 ](NO 3 ) 2 and C 12 EO 10 is C 12 H 25 -(OCH 2 CH 2 ) 10 OH) lyotropic liquid crystalline (LLC) mesophase with a drastic dropping on the melting point of ZnX. The salt-surfactant LLC mesophase is stable down to -52°C and undergoes a phase change into a solid mesostructured salt upon cooling below -52°C; no phase separation is observed down to -190°C. The ZnX-C 12 EO 10 mesophase displays a usual phase behavior with an increasing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
54
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 28 publications
(55 citation statements)
references
References 24 publications
0
54
1
Order By: Relevance
“…This is a well-known physicochemical behavior of solutions (known as colligative properties and depression of the melting point of solvents in the presence of impurities). Therefore similar physicochemical phenomena are happening in a confi ned space at much lower temperatures [ 10 ] in the hydrophilic domains of the mesophases. Otherwise, it is impossible to keep the salt species in the mesostructures at such high concentrations (higher than the solubility limit of the salts in water).…”
Section: Mesoporous Meso-zn 2 Tio 4 and Meso-cdtio 3 Thin Filmsmentioning
confidence: 89%
See 2 more Smart Citations
“…This is a well-known physicochemical behavior of solutions (known as colligative properties and depression of the melting point of solvents in the presence of impurities). Therefore similar physicochemical phenomena are happening in a confi ned space at much lower temperatures [ 10 ] in the hydrophilic domains of the mesophases. Otherwise, it is impossible to keep the salt species in the mesostructures at such high concentrations (higher than the solubility limit of the salts in water).…”
Section: Mesoporous Meso-zn 2 Tio 4 and Meso-cdtio 3 Thin Filmsmentioning
confidence: 89%
“…[ 9 ] We recently found that salt-surfactant LLC self-assembly occurs because the salt melts and acts as a solvent in the assembly process. [ 10 ] Note also that in a confi ned space (the hydrophilic domains of the mesophase), the melting point of the salt drops drastically and the molten salt never crystallize even down to liquid nitrogen temperatures due to the soft confi nement effect (SCE). [ 10 ] The addition of a charged surfactant to the salt-oligo(ethylene oxide) non-ionic surfactant LLC phase further increases the amount of salt in the LLC mesophase.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our attention focuses on the influence on the material structure of (i) the presence of the block copolymer and (ii) the nature of the manganese salt used as the precursor. Block copolymers have been shown to form complexes with metal cations [54][55][56]. Manganese oxide could be introduced either inside the titania walls or at the titania surface by choosing a good manganese precursor having more or less affinity either with the polymer and/or with the titania sol.…”
Section: Introductionmentioning
confidence: 99%
“…1 Organizing surfactants into lyotropic liquid crystalline (LLC) mesophases by using molten salts can be beneficial in the production of new materials for clean energy applications. 2,3 Recently, we have demonstrated that the molten phase of salts can be used as a solvent in the synthesis of mesoporus metal oxide modified silica 2 as well as titania.…”
Section: ■ Introductionmentioning
confidence: 99%